Automated Solvent‐Free Polymerization of Hyperbranched Polyglycerol with Tailored Molecular Weight by Online Torque Detection. Issue 7 (21st May 2021) - Wallert, Matthias; Plaschke, Johann; Dimde, Mathias; Ahmadi, Vahid; Block, Stephan; Haag, Rainer
Abstract: Polymerization processes with high reproducibility, traceability, and nontoxic compounds are required for biomedical applications. Here an automated solvent‐free polymerization of hyperbranched polyglycerol has been established on a multiple‐hundred gram scale. Performed is an anionic ring‐opening multibranching (ROMB) polymerization with slow addition of glycidol. The solvent‐free approach avoids commonly used organic solvents during the polymerization and work‐up. Due to the automation of the polymerization process a high reproducibility and traceability is accomplished. The used reactor is equipped with an anchor stirrer and stirrer control, which measures the applied torque. A linear correlation of the increasing torque and the degree of polymerization is observed, which can be used to monitor the molecular weight in situ during the polymerization. Abstract : An automated solvent‐free polymerization of hyperbranched polyglycerol is developed to generate reproducible, biocompatible, noncytotoxic, and water‐soluble polymers for biomedical applications. The empirically investigated correlation between the relative torque and the corresponding molecular weight enables to monitor the molecular weight online during polymerization. ​